Use of Fourier-Domain Optical Coherence Tomography to Evaluate Anterior Stromal Opacities in Donor Corneas - Matthew R. Bald; Christopher Stoeger; Joshua Galloway; Maolong Tang; Jeffrey Holiman; David Huang (Journal of Ophthalmology)
Purpose. To evaluate Fourier-domain optical coherence tomography (FD-OCT) as an adjunct to traditional slit lamp examination of donor corneas with suspected Anterior Stromal Opacities. Methods. Seven corneas suspected of having anterior stromal opacities by slit lamp examination were evaluated with FD-OCT. Each cornea was evaluated to confirm the presence of opacity and, if present, the depth of opacity was measured. Results. The opacity depth ranged from 82 μm to 624 μm. The initial slit lamp impressions of five of the seven corneas were confirmed by OCT. In two corneas, the OCT findings were different from the initial slit lamp impressions. Slit lamp examination of the first cornea gave the impression of anterior stromal scarring, but OCT showed that the opacity was limited to the epithelium. Slit lamp examination of the second cornea suggested opacity limited to the epithelium, but OCT identified significant sub-Bowman's scarring. In all cases, the Eye Bank Technicians reported that the location and depth of corneal opacity were more sharply defined by OCT than by slit lamp. Conclusion. The high resolution of OCT makes it easier to determine the location of corneal opacities compared to slit lamp examinations. This enhanced visualization can improve decisions regarding transplant suitability of donor corneas.